Development of products with Shiitake mushroom: chemical, physical and sensory characterization - Guiné, Raquel (2019)
Shiitake mushrooms are much appreciated and therefore their production has increased. However, an important quantity of by-products and residues, are also generated and which are considered as waste materials. In this way, the aim of this work was to develop new foods incorporating shiitake mushrooms that do not comply with standards for commercialization, thus providing additional sources of income for the farmers. For this, a filling with mushroom was produced for rissoles and pies, and the final products were analysed for their chemical composition, colour, texture and sensorial attributes. The results showed that the shiitake products presented an interesting chemical composition, rich in protein and minerals, and poor in salt. It was also observed that the frying operation induced more colour changes in the rissoles than the oven baking of the pies. The textural measurements indicated that the rissoles were much softer when compared to the pies, being also more cohesive and elastic. The sensory panel attributed high scores to both products (around 4.5, on a scale from 1 to 5), thus indicating that these may constitute an additional source of income to the farmers and at the same time reducing waste.